Assessment of factors and interventions towards therapeutic adherence among persons with non-cystic fibrosis bronchiectasis. Issue 4 (7th November 2022) - Thornton, Christina S.; Somayaji, Ranjani; Lim, Rachel K.
Non-cystic fibrosis bronchiectasis (NCFB) is a highly prevalent chronic respiratory disease with substantial burden to both patients and healthcare systems. Persons with NCFB (pwNCFB) are often given complex acute and chronic treatment regimens consisting of medications, airway clearance techniques and exercise. Accordingly, the high burden in NCFB has contributed to lower therapy adherence, with estimates of 53% to medications, 41% to airway clearance and only 16% to all prescribed therapy. Consequent clinical outcomes from lower adherence include reduced quality of life, accelerated lung function decline and recurrent pulmonary exacerbations. In this narrative review, we explore the impact of multifactorial mechanisms underpinning adherence in NCFB and evaluate the available evidence towards interventions to improve uptake of therapy as demonstrated in other chronic respiratory diseases. A holistic approach, starting with a careful review of patient adherence at regular intervals, may increase the success of multidimensional therapeutic interventions in pwNCFB, but robust ongoing studies are an area of need in this population. Adherence to therapy is a complex interplay of multiple factors with significant impact on clinical outcomes. This is the first comprehensive review evaluating the evidence and challenges surrounding such adherence interventions in bronchiectasis. https://bit.ly/3TcvnqX